LEGAL STUDY OF COLLECTIVE LABOR AGREEMENTS BY COMPANIES CONDUCTING COMPANY MERGER IN IMPROVING WORKFORCE WELFARE (Study of the Merger of PT Pelabuhan Indonesia (Persero)) - Salsabillah, Neifa; Abduh, Rachmad (Inspiring Law Journal, 2024)
The development of the Indonesian economy has also colored the pattern of Indonesian business development. This is indicated by the increasing number of companies in the trade and service sectors that carry out mergers. Where the merger of PT Pelabuhan Indonesia (Persero) or Pelindo, which is a merger of state-owned ports that officially merged on October 1, 2021. The consequences of the merger action on the welfare of the workforce in each of the previous companies must be the responsibility of the company resulting from the merger. This research method uses this type of research is a type of empirical juridical legal research using a statutory approach to the Legal Study of Collective Labor Agreements by Companies Merging Companies in Improving Labor Welfare (Study of the Merger of PT Pelabuhan Indonesia (Persero)). as for what is meant by empirical juridical legal research is research conducted by analyzing problems by combining legal materials (which are secondary data) with primary data obtained in the field. Based on the research conducted, the reason for the merger or merger of PT Pelabuhan Indonesia or Pelindo is an important step to increase the effectiveness and efficiency of national ports. Based on the agreement of the collective labor agreement between PT Pelabuhan Indonesia (Pelindo) and SPPIB 2023-2025, it was agreed to continue using the PKB from each region. The obstacles experienced by the merged company in an effort to improve the welfare of the workforce regarding employee benefits contained in PSAK24 where equalization cannot be made to all regional sub-holdings of PT Pelabuhan Indonesia (Persero) or Pelindo. The company provides legal assistance in order to improve the welfare of the workforce as a form of corporate responsibility to fulfill its obligations in the ongoing employment relationship between the company and the workforce